Multifarious anchovy and sardine regimes in the Humboldt Current System during the last 150 years. (12th December 2017) - Salvatteci, Renato; Field, David; Gutiérrez, Dimitri; Baumgartner, Tim; Ferreira, Vicente; Ortlieb, Luc; Sifeddine, Abdel; Grados, Daniel; Bertrand, Arnaud
Abstract: The Humboldt Current System (HCS) has the highest production of forage fish in the world, although it is highly variable and the future of the primary component, anchovy, is uncertain in the context of global warming. Paradigms based on late 20th century observations suggest that large‐scale forcing controls decadal‐scale fluctuations of anchovy and sardine across different boundary currents of the Pacific. We develop records of anchovy and sardine fluctuations since 1860 AD using fish scales from multiple sites containing laminated sediments and compare them with Pacific basin‐scale and regional indices of ocean climate variability. Our records reveal two main anchovy and sardine phases with a timescale that is not consistent with previously proposed periodicities. Rather, the regime shifts in the HCS are related to 3D habitat changes driven by changes in upwelling intensity from both regional and large‐scale forcing. Moreover, we show that a long‐term increase in coastal upwelling translates via a bottom‐up mechanism to top predators suggesting that the warming climate, at least up to the start of the 21st century, was favorable for fishery productivity in the HCS. Abstract : We develop records of anchovy and sardine fluctuations in the Humboldt Current System since 1860 AD using fish scales from multiple sites containing laminated sediments and compare them with Pacific basin‐scale and regional indices of ocean climate variability. Our records reveal two main anchovy and sardine regimes that are related to 3D habitat modifications driven by upwelling intensity changes from both regional and large‐scale forcing. Additionally, a long‐term increase in coastal upwelling translates via a bottom‐up mechanism to top predators suggesting that the warming climate, at least up to the start of the 21st century, was favorable for fishery productivity.